2006
DOI: 10.1074/jbc.m513054200
|View full text |Cite
|
Sign up to set email alerts
|

Plant Sulfite Oxidase as Novel Producer of H2O2

Abstract: Sulfite oxidase (EC 1.8.3.1) from the plant Arabidopsis thaliana is the smallest eukaryotic molybdenum enzyme consisting of a molybdenum cofactor-binding domain but lacking the heme domain that is known from vertebrate sulfite oxidase. While vertebrate sulfite oxidase is a mitochondrial enzyme with cytochrome c as the physiological electron acceptor, plant sulfite oxidase is localized in peroxisomes and does not react with cytochrome c. Here we describe results that identified oxygen as the terminal electron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…It has been shown that the molybdenum center of the plant enzyme reacts with O 2 directly, with H 2 O 2 as the ultimate product of the reaction. 313 It has subsequently been demonstrated, however, that O 2 •− is the immediate product of the reaction, and that H 2 O 2 is formed only indirectly by the spontaneous disproportionation of O 2 •−.314 The observed rate constant for the reaction of reduced enzyme with O 2 exhibits a linear dependence on [O 2 ] ( k ox = 5.3 × 10 4 M −1 s −1 at pH 8.0); given that the rate of reduction of the plant enzyme by sulfite exceeds that accessible by stopped-flow, 308 the oxidative half-reaction is clearly rate-limiting for overall turnover with the plant enzyme. Plant sulfite oxidase is localized in the peroxisome, and it is possible that the superoxide it generates is involved in antimicrobial generation of reactive oxygen species, although an appropriate source of sulfite to provide the reducing equivalents necessary for generation of a superoxide burst upon infection has not been identified.…”
Section: The Sulfite Oxidase Familymentioning
confidence: 99%
“…It has been shown that the molybdenum center of the plant enzyme reacts with O 2 directly, with H 2 O 2 as the ultimate product of the reaction. 313 It has subsequently been demonstrated, however, that O 2 •− is the immediate product of the reaction, and that H 2 O 2 is formed only indirectly by the spontaneous disproportionation of O 2 •−.314 The observed rate constant for the reaction of reduced enzyme with O 2 exhibits a linear dependence on [O 2 ] ( k ox = 5.3 × 10 4 M −1 s −1 at pH 8.0); given that the rate of reduction of the plant enzyme by sulfite exceeds that accessible by stopped-flow, 308 the oxidative half-reaction is clearly rate-limiting for overall turnover with the plant enzyme. Plant sulfite oxidase is localized in the peroxisome, and it is possible that the superoxide it generates is involved in antimicrobial generation of reactive oxygen species, although an appropriate source of sulfite to provide the reducing equivalents necessary for generation of a superoxide burst upon infection has not been identified.…”
Section: The Sulfite Oxidase Familymentioning
confidence: 99%
“…In this process, substrate-derived electrons are transferred to molecular oxygen with formation of superoxide anions (Byrne et al, 2009) and hydrogen peroxides (Haensch et al, 2006). In the physiological context, SO represents a part of an intracellular sulfite homeostasis network required to prevent plant cells from the toxic effects of endogenously arising sulfite (Brychkova et al, 2007; Lang et al, 2007).…”
Section: Molybdenum Cofactor and Molybdenum-dependent Enzymesmentioning
confidence: 99%
“…In bacteria, sulfite oxidation is often linked to energy-generating processes during chemolithotrophic growth on reduced sulfur compounds (2, 3), whereas both plant and vertebrate sulfite oxidases have been shown to detoxify sulfite arising from the degradation of methionine and cysteine and exposure to sulfur dioxide (4,5).…”
mentioning
confidence: 99%